Anti-inflammatory Effects of GTE in Eye Diseases - Li, Jian; Du, Lin; He, Jing Na; Chu, Kai On; Guo, Cosmos Liutao; Wong, Mandy Oi Man; Pang, Chi Pui; Chu, Wai Kit (Frontiers in Nutrition, 2021)
Ocular inflammation is a common complication of various eye diseases with wide consequences from irritations to potentially sight-threatening complications. Green tea is a popular beverage throughout the world. One of the proven health benefits of consuming green tea extract (GTE) is anti-inflammation. Catechins are the biologically active constituents of GTE. In in vitro and in vivo studies, GTE and catechins present inhibition of inflammatory responses in the development of ocular inflammation including infectious, non-infectious or autoimmune, and oxidative-induced complications. Research on the ocular inflammation in animal models has made significant progress in the past decades and several key disease mechanisms have been identified. Here we review the experimental investigations on the effects of GTE and catechins on various ocular inflammation related diseases including glaucoma, age-related macular degeneration, uveitis and ocular surface inflammation. We also review the pharmacokinetics of GTE constituents and safety of green tea consumption. We discuss the insights and perspectives of these experimental results, which would be useful for future development of novel therapeutics in human.